Cigarettes smoking and the risk of rehospitalization in patients with schizophrenia - Karakuła, Hanna; Pawełczak, Paweł; Stecka, Mariola (Current Problems of Psychiatry, 2012)
Schizophrenia is a chronic mental disease which, in spite of adequate treatment, brings a high risk of relapse with frequent need for hospitalization. Among many factors affecting the frequency of hospitalization in patients diagnosed with schizophrenia, smoking cigarettes is one of them. Numerous research confirmed higher percentage of smoking schizophrenic patients as compared to patients suffering from other mental illnesses or healthy population. The prevalence of nicotine dependence among schizophrenic patients is explained, inter alia, by relationship with disease symptoms and side effects of the treatment and related attempts of self-medication. Lower premorbid functioning, more acute disease process, higher risk of relapse and somatic disease, are observed in smoking patients group diagnosed with schizophrenia. The course of schizophrenic process could be modified by smoking, through 1) neurobiological changes, as increasing of dopamine activity, 2) enzyme induction responsible for the drug metabolism, and related to this process changes of plasma concentration of neuroleptics. Complexity of the relation between smoking, course of schizophrenic process and risk of rehospitalisation, cannot draw definite conclusions and should be inspiration for further research.